Public buying behaviors during the COVID-19 pandemic: the influence of attitude and perceived social norms from a presumed media influence perspective - Goh, Tong Jee; Ho, Shirley S. (Frontiers in Communication, 2023)
Episodes of mass buying occurred in many parts of the world during the COVID-19 pandemic in 2020. This study applied the influence of presumed media influence model (IPMI) model to examine the development of the intention to make more purchases during the pandemic in Singapore. The results, which were based on a sample of 1,007 Singaporeans, showed that the presumption of media influence on others positively predicted the intention to make more purchases, through the attitude toward making more purchases and the perceived subjective norms of making more purchases. These psychological and behavioral outcomes were associated with people's attention to the media content that reflected the mass-buying episodes in Singapore and the government's attempt at assuring the citizens that the country maintains an ample supply of goods during the pandemic. The positive associations in the IPMI model lend a media and communication perspective to explain the common proposition that consumers reacted to the social norms of making more purchases during the pandemic. The theoretical implications for future IPMI studies and practical implications for key stakeholders are discussed.